2021
DOI: 10.1111/gcbb.12797
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate change and climate extremes on sugarcane production

Abstract: Sugarcane production supports the livelihoods of millions of small‐scale farmers in developing countries, and the bioenergy needs of millions of consumers. Yet, future sugarcane yields remain uncertain due to differences in climate projections, and because the sensitivity of sugarcane ecophysiology to individual climate drivers (i.e. temperature, precipitation, shortwave radiation, VPD and CO2) and their interactions is largely unresolved. Here we ask: how sensitive is sugarcane yield to future climate change,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…Nevertheless, we found that if temperatures above 35°C become more frequent in the future, a decline in net carbon uptake is expected to affect sugarcane yields if the crop does not adapt (Figures 3a and 9). This agrees with the recent findings of Flack‐Prain et al (2021), where temperature is the main driver for sugarcane yield decline in future projections for São Paulo, Brazil. In their study, the Soil–Plant–Atmosphere model was employed which simulates photosynthesis at sub‐daily timestep.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, we found that if temperatures above 35°C become more frequent in the future, a decline in net carbon uptake is expected to affect sugarcane yields if the crop does not adapt (Figures 3a and 9). This agrees with the recent findings of Flack‐Prain et al (2021), where temperature is the main driver for sugarcane yield decline in future projections for São Paulo, Brazil. In their study, the Soil–Plant–Atmosphere model was employed which simulates photosynthesis at sub‐daily timestep.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to inducing quantitative and qualitative losses in production, excessive heat shortens the crop cycle's duration, reducing the leaf area accelerating metabolism, consequently causing early plant senescence. Photosynthesis is one of the physiological processes most sensitive to heat (Demirevska-Kepova et al, 2005;Flack-Prain et al, 2021) due to the sensitivity of the thylakoid membrane, the structure where chloroplasts are contained, damage caused by excess heat causes a reduction in chlorophyll production (Ristic et al, 2007;Sharma et al, 2022).…”
Section: Falker Chlorophyll Indexes (Fci)mentioning
confidence: 99%
“…Abiotic stresses such as drought, salinity, extreme temperature, and low soil fertility also affect sugarcane growth and yield worldwide ( Lakshmanan and Robinson, 2014 ; Budeguer et al, 2021 ). Drought is the most important abiotic factor and can reduce sugarcane yield by up to 50–60% ( Ferreira et al, 2017 ; Flack-Prain et al, 2021 ). Generally, plants or organs responding to water stress exhibit physiological and metabolic changes to minimize water loss under moderate-to-severe short-term stress ( Lakshmanan and Robinson, 2014 ; Ferreira et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%